DINAMIKA MAKNA SIMBOLIK UANG PANAIK DALAM PERSPEKTIF SOSIOLOGI KONTEMPORER (STUDI STRATIFIKASI SOSIAL DAN MOBILITAS VERTIKAL) - Kumala, Andi; Jumadi, Jumadi; Suhaeb, Firdaus W; Najamuddin, Najamuddin (Social Landscape Journal, 2025)
This article will discuss the dynamics of the symbolic meaning of bride price in the era of modern society in Soppeng Regency. The research method used in this study is qualitative research employing a descriptive approach. The results of this study indicate that the dynamics of the symbolic meaning of bride price in the modern era of society in Soppeng Regency can be seen from the way the bride price is given, namely, first, it is handed over during the official engagement ceremony attended by the extended family of women and community leaders. Second, the presentation occurs when the groom comes along with his dowry (belongings) escorted by the extended family of the groom during the marriage ceremony. The tradition of giving bride price is maintained because it is a cultural practice that holds significant symbolic meaning and value for the community in Lalabata District, Soppeng Regency, even though the bride price: First, it becomes an obstacle to marriage for both men and women. Second, it compels or forces men to go into debt. Third, it encourages elopement marriages. Fourth, many women choose not to marry and remain spinsters because potential suitors abandon their intentions to marry.